1980
DOI: 10.1093/nar/8.1.85
|View full text |Cite
|
Sign up to set email alerts
|

The structure of drug-deoxydinucleoside phosphate complex; generalized conformational behavior of intercalation complexes with RNA and DNA fragments

Abstract: A 2:2 complex of proflavine and deoxycytidylyl-3', 5'-guanosine has been crystallized and its structure determined by x-ray crystallography. The two dinucleoside phosphate strands form self complementary duplexes with Watson Crick hydrogen bonds. One proflavin is asymmetrically intercalated between the base pairs and the other is stacked above them. The conformations of the nucleotides are unusual in that one strand has C3',C2'endomixed sugar puckering and the other has C3',C3' endo deoxyribose sugars. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(70 citation statements)
references
References 17 publications
3
66
0
Order By: Relevance
“…Thus far, our attempts to use intercalators to drive the polymerization of mononucleotides and dinucleotides in the absence of a preexisting template strand have proven unsuccessful. In the case of dinucleotides, we surmise that the nearest neighbor exclusion principle (46)(47)(48), which states that intercalators can bind at most between every other base pair, could potentially inhibit the coupling of dinucleotides, as dinucleotides are known to crystallize in the presence of intercalators with ligands bound both within and outside each minihelix (49), an arrangement that could block backbone coupling between dinucleotides. To find a possible means by which to circumvent this problem, we have initiated studies of intercalation of nucleic acids with alternative backbone linkages (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, our attempts to use intercalators to drive the polymerization of mononucleotides and dinucleotides in the absence of a preexisting template strand have proven unsuccessful. In the case of dinucleotides, we surmise that the nearest neighbor exclusion principle (46)(47)(48), which states that intercalators can bind at most between every other base pair, could potentially inhibit the coupling of dinucleotides, as dinucleotides are known to crystallize in the presence of intercalators with ligands bound both within and outside each minihelix (49), an arrangement that could block backbone coupling between dinucleotides. To find a possible means by which to circumvent this problem, we have initiated studies of intercalation of nucleic acids with alternative backbone linkages (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…From the crystal data about the Acridine Orange cation (Obendorf et al 1976;Reddy et al 1979;Mattia et al 1984Mattia et al , 1995Kuban et al 1985;Gordon et al 2003), the Proflavine cation (Jones and Neidle 1975;Shieh et al 1980Shieh et al , 1982Swaminathan et al 1982;Aggarwal et al 1984;Ara and El Bahij 2004;Varga et al 2007), Methylene Blue (Marr et al 1973;Kahn-Harari et al 1973;Endres et al 1977;Snaathorst et al 1981;Enescu et al 2000;Sours et al 2002;Kavitha et al 2004;Li et al 2005;Soneta and Miyamura 2006;Raj et al 2007), Eosin (Harrison et al 2007), Rhodamine B (Fujii et al 1995;Nishikiori and Fujii 1997;Soneta et al 2006), Ethyl Rhodamine G (Wang et al 1997;Fun et al 1997;Liu et al 1998;Adhikesavalu et al 2001;Zhang et al 2001), Para-rosaniline (Koh and Eriks 1971;Liu et al 2002;Xie 2008), and Crystal Violet (Spangler et al 1989;Lovell et al 1999;Lacour et al 2002;Soneta et al 2006), as well as the substituted 1-phenyl-azo-2-naph...…”
Section: Dye Aggregatesmentioning
confidence: 99%
“…So far the P2,2,2 space group has only been observed for one form of tetranucleotide d(B'CCGG) (Conner et al, 1984) which structure has not yet been reported, and for dinucleotides. Most of them are complexed with intercalating drugs, d(GpG)-cisplatin (Sherman et al, 1988), d(CpG)-dimethylproflavine (Sakore et al, 1984), d(CpG)-proflavine (Shieh et al, 1980), d(pTpT)-Na' salt (Camerman et al, 1976), r(ApA)-proflavine (Neidle et al, 1978) and r(ApA)-Ca' salt (Einspahr et al, 1981). However, the length of a dinucleotide hardly reflects a helical structure close to the natural DNA-type double helices.…”
mentioning
confidence: 99%